Inward FDI, value added and employment in US states: A panel cointegration approach - Elias Ajaga; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2008)
This study investigates the long-run relationships between inward FDI and economic outcomes in terms of value added and employment at the level of US states. Johansen's (1988) cointegration technique and Toda and Yamamoto's (1995) Granger causality tests are applied to data for the period of 1977 to 2001. We find cointegration as well as two-directional causality between FDI and outcome variables. This holds for both measures of FDI (stocks and employment in foreign affiliates) and independently of whether we consider the states' overall economy or their manufacturing sector.
Keywords: O51; F23; O18; 330; FDI-related employment; Gross state product; Manufacturing; Granger causality; FDI stocks; Direktinvestition; Ausländisch; Teilstaat; Wertschöpfung; Beschäftigungseffekt; Regionale Entwicklung; USA